2023
DOI: 10.3389/fendo.2023.1043370
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes in low and middle-income countries - Tanzania a streak of hope

Abstract: IntroductionIn several of the Low and Middle Income countries , many patients with Type 1 diabetes (T1D) are most probably not diagnosed at all which may contribute to their low incidence. As an example of a country with low income and poor resources, we have chosen to study T1D in children/young people in Tanzania.MethodsAnalyses of casebooks and statistics at several Tanzanian hospitals treating young patients with insulin dependent diabetes, usually Type 1 diabetes, and collection of information from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…This finding is lower than a study conducted Tanzania, 38.3% of DKA prevalence in 2022 despite the fact that the nation DKA trend was decreased over time, from 89.9% in 2005. 30 Another retrospective study conducted in Benin teaching hospital found the frequency of DKA in newly diagnosed adults to be 77.1%. 31 This frequency is higher relatives to our study, and this might be due to the Benin study, included adults b/n 15–35 years of age and because the study period was 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is lower than a study conducted Tanzania, 38.3% of DKA prevalence in 2022 despite the fact that the nation DKA trend was decreased over time, from 89.9% in 2005. 30 Another retrospective study conducted in Benin teaching hospital found the frequency of DKA in newly diagnosed adults to be 77.1%. 31 This frequency is higher relatives to our study, and this might be due to the Benin study, included adults b/n 15–35 years of age and because the study period was 15 years.…”
Section: Discussionmentioning
confidence: 99%